Acupoint application and nursing for relief of low back pain in a patient with chronic kidney disease (穴位贴敷治疗1例慢性肾脏病腰酸腰痛患者的护理) - LIU Sichun (刘司春); YANG Mingying (杨明颖); TANG Ling (唐玲); DENG Jianhua (邓建华) (Association of Integrative Nursing, 2022)
This paper reported the acupoint application and nursing management for relief of low back pain in a patient with chronic kidney disease. The prescription of Chinese herbal medicine used in acupoint application, operation method and cautions were introduced. A set of targeted interventions including nursing assessment, illness observation, psychological nursing and dietary guidance were carried out for relief of low back pain and improve the activity of daily living of the patient. (本文总结1例慢性肾脏病腰酸腰痛患者应用穴位贴敷治疗的护理经验, 主要包括穴位贴敷的药方组成、操作方法、注意事项以及相关护理评估、病情观察、心理干预、饮食指导等措施。通过穴位贴敷配合针对性护理措施, 能够有效改善患者腰酸腰痛症状, 提高日常活动能力。)